Attitudes of the Diyala Government audience towards the misleading news of the formation of the Iraqi government for 2022 (Journal of Namibian Studies : History Politics Culture, 2023)
This study aims to find out “the attitudes of the Diyala government towards the misleading media of the formation the Iraqi government". Also, disinformation in the midst of the growing contemporary political bets is one of the contemporary media practices, based on lying, misinformation, deception and manipulation of facts. Through these bases, these facts are fabricated and alternative facts are presented to the existing reality and published in systematic forms in the public domain until they turn over time into a real tangible reality.The researcher expanded, by drawing a sample using a sample, the snowball, which is one of the 400 non-probable samples to identify the attitudes of the Diyala governorate public towards the misleading media to form the Iraqi government. The study questionnaire was prepared from theoretical literature and previous studies, and the validity of the questionnaire was confirmed by apparent honesty. Also, the stability of the scale was confirmed by the Cronbach's alpha equation. The study found that the reasons for the spread of misleading news about the formation of the government are the lack of public confidence in the government, due to the poor conditions within society, and the wrong understanding of information and lack of knowledge of it.